Comparison of the Film Properties of Lemon and Sour Cherry Seed Essential Oil-Added Glycerol and/or Sorbitol-Plasticized Corn, Potato, Rice, Tapioca, and Wheat Starch-Based Edible Films - Kazak, Merve Basut; Tugrul, Nurcan (WILEY, 2024)
In this study, lemon, and sour cherry seed essential oil-added glycerol and/or sorbitol-plasticized corn, potato, rice, tapioca, and wheat starch-based edible films were produced using the casting method. Starch, essential oil type and glycerol and/or sorbitol effects on the thickness, moisture content, water solubility, swelling index, and water vapor transmission rate of the films have been studied. The interaction of the film components was evaluated by Fourier transform infrared spectroscopy. It was seen that wheat starch-based control films give the lowest thickness value (0.010 mm). Wheat starch-based control films (15.50%), sour cherry seed essential oil-added corn starch (17.80%), and lemon essential oil-added rice starch-based composite films (17.70%) have high moisture content. The lowest solubility values were obtained from wheat starch control (22%) and sour cherry seed essential oil-added corn starch composite (16.40%) films. The highest swelling index values were obtained from wheat starch-based control (210.90-289.0%), sour cherry seed essential oil-added tapioca starch (388.80%), and lemon essential oil-added potato starch-based (433.20%) composite films. Rice starch-based control films have the lowest water vapor transmission rate (3.30x10-8-5.70x10-8). FTIR spectra of edible composite films proved that there is no chemical interaction between the film component and that they kept their structure. The main difference of this study from previous studies was the use of sour cherry seed essential oil for the first time in edible film production and the comparison of the film properties of corn, potato, rice, tapioca, and wheat starch-based edible films plasticized with glycerol or sorbitol.
Keywords: ENCAPSULATION; PECTIN; GUM; Polymer Science